DESKRIPSI KETERLAKSANAAN PENDEKATAN SAINTIFIK DALAM PEMBELAJARAN MATEMATIKA DI MTs DARUL ULUM KOTABARU - Dzulfitri Dzulfitri; Rahmi Yuliana M (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2018)
Abstract This study aims to determine the feasibility of categories and descriptions of scientifics approaches in the study of mathematics at MTs Darul Ulum Kotabaru which includes planning and implementation. This study is a qualitative research where the main instrument in this study are researcher themselves, guided by the observation sheet and interview guide. The subjects were mathematics teacher who taught in class VII (seven) as much as two people who were selected purposively by consideration of both has been training in 2013 curriculum and implement in the classroom.Data collection was conducted by observation and semi-structured interviews. The collected data were analyzed qualitatively. The results show that: in designing the scientifics study, subjects SM is in good categories and the implementation is in fair category, while subject NJ in the planning and implementation is in poor category. Results reveal that the description of subject SM in planning the learning scenario general description of learning characteristics is clearly illustrated but students’ activities related to scientifics characteristics are not descrbed in their entirety within the RPP, particularly data collection and associating, both of these activities clearly illustrased in LKPD. Subject SM in preparing lesson plan related to LKPD, so the student and teacher’s activity in observation is in sync between the activities observed in the RPP and its implementation, the teachers’ activities in gathering information ang associating in planning formulated are not described scientificly but both of these aspects portrayed in LKPD, so it is implemented well. While the planning formulated describe scientific such as the step of communicating but did not take place in practice. In planning, subject NJ in observation activities, asking questions, and communicating formulated plan described scientific, but did not take place in practice. While the activity of collecting information and associate in formulated plan did not describe scientific but implemented in practice.Key word: deskripsi keterlaksanaan pembelajaran, kurikulum 2013, pendekatan saintifik, matematika.